Influência de distúrbios abióticos na qualidade da madeira de eucalipto para produção de celulose - Silva, Ana Paula Câmara da (2016)
The production sustainability of Eucalyptus is threatened when there are diseases and growth disorders that can be of abiotic origin and compromise the wood quality of the, resulting from the adverse environmental conditions of the plantations. Thus, it should be to evaluate the influence of different levels of abiotic disturbances in Eucalyptus grandis x Eucalyptus urophylla for the production of pulp and group them according to the similarities of the variables. From age 7 trees were collected in the municipalities of Vila Nova DOS Martírios and Imperatriz, Maranhao, Brazil, and classified according to severity of symptoms observed visually. The results of characterization dendrometric, anatomical, chemical and density as well as Kraft pulping parameters of wood were compared and showed that the intensity of the symptoms of disorders changed the quality of pulpwood. It is noteworthy that, for the most severe disturbance level, the best results for dendrometric variables were obtained, basic density, vascular diameter, fiber and specific consumption of wood. No significant differences were observed in levels of lignin and pentosans due to the occurrence of the disorder abiotic. The use of multivariate analysis identified the variability of the properties of wood, having the characteristics of fibers, length and wall thickness of greater importance in scoring differences of abiotic disturbance levels. With the grouping, formed two groups: one with the junction of levels I and II of abiotic disorder and another, with the level III, it is possible to infer that the homogenization of materials as the group tends to improve the volume and density wood pulp production.